Validation of an improved Anaplasma antibody competitive ELISA for detection of Anaplasma ovis antibody in domestic sheep. (September 2017) - Mason, Kathleen L.; Gonzalez, Michael V.; Chung, Chungwon; Mousel, Michelle R.; White, Stephen N.; Taylor, Joshua B.; Scoles, Glen A.
An accurate and simple-to-perform new version of a competitive ELISA (cELISA) kit that became commercially available in 2015 for testing of cattle for antibody to Anaplasma marginale was validated for detection of Anaplasma ovis antibody in domestic sheep. True positives and negatives were identified using nested PCR (nPCR) as the gold standard. Negative bovine control sera supplied with the kit were used to calculate % inhibition (%I), designated bovine control ELISA (BcELISA), and this was compared to %I calculated from negative ovine sera derived from hand-raised, pathogen-free sheep, designated ovine control ELISA (OcELISA). The receiver operating characteristics area under the curve was 1.0 with a p value <0.001 regardless of the source of the control sera. The cutoff values for negative BcELISA and OcELISA were <30%I and <27%I, respectively. Our work confirmed that this Anaplasma antibody cELISA kit version 2 can be used with the serum controls supplied in the kit to test for A. ovis antibody in domestic sheep. Furthermore, this work confirmed the historically high infection prevalence (>93%) at the U.S. Sheep Experiment Station (Dubois, Idaho), in spite of efforts to reduce the possibility for iatrogenic transmission there, suggesting high levels of tick-borne transmission.